2005
DOI: 10.1074/jbc.m507587200
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Peroxidation Induces Cholesterol Domain Formation in Model Membranes

Abstract: Numerous reports have established that lipid peroxidation contributes to cell injury by altering the basic physical properties and structural organization of membrane components. Oxidative modification of polyunsaturated phospholipids has been shown, in particular, to alter the intermolecular packing, thermodynamic, and phase parameters of the membrane bilayer. In this study, the effects of oxidative stress on membrane phospholipid and sterol organization were measured using small angle x-ray diffraction appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
91
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(98 citation statements)
references
References 79 publications
(53 reference statements)
6
91
0
Order By: Relevance
“…11,12 Second, previous studies, including an earlier report of BMES, 3 used only MetS data at baseline in the evaluation of its relationship with cataracts. However, experimental studies in rats and humans have shown that the effect of glucose and lipid abnormalities on cataract formation may change over time 12,13 ; therefore, this underscores the importance of collecting further information on glucose and lipid abnormalities beyond baseline measurements to better detect cataract formation.…”
Section: Resultsmentioning
confidence: 99%
“…11,12 Second, previous studies, including an earlier report of BMES, 3 used only MetS data at baseline in the evaluation of its relationship with cataracts. However, experimental studies in rats and humans have shown that the effect of glucose and lipid abnormalities on cataract formation may change over time 12,13 ; therefore, this underscores the importance of collecting further information on glucose and lipid abnormalities beyond baseline measurements to better detect cataract formation.…”
Section: Resultsmentioning
confidence: 99%
“…Lipid peroxidation triggered by free radicals in isolated membrane is known to enhance formation of membrane-restricted cholesterol domains through selfassociated cholesterol monomers (46). Similar to other flavonoids, the inhibition of lipid peroxidation by Q3G may be attributed to the presence of an o-dihydroxyl group (25).…”
Section: Discussionmentioning
confidence: 99%
“…2 and 12 ). Phospholipid oxidation promotes cholesterol-domain formation ( 198 ), and these domains are distinct from those formed with nonoxidized membranes ( 199 ). The relative amount of cholesterol is lowest in the outer cortical region of the lens where the molar cholesterol-phospholipid ratio is 1:2 ( 197,200,201 ).…”
Section: Cataract Lens Lipids Lifespan and Mortalitymentioning
confidence: 97%